THE MISSION OF THE CATHOLIC CHURCH IN PROMOTING PEACE AND RECONCILIATION IN THE CONTEMPORARY WORLD - Alva, Reginald (Asian Horizons, 2017)
Peace, reconciliation and mercy are the attributes of the Triune God. The Catholic Church’s mission is to be the living sign of God’s peace and reconciliation in the contemporary world, which is being torn apart by conflicts and strife. There is widespread unrest between nations, groups and individuals on various issues. Modern people are hoping against hope to see a world, where peace, reconciliation and mercy flourish. In this paper, we shall examine theologically the mission of the Catholic Church in promoting peace, reconciliation and mercy in the contemporary world. The primary resources for our study are Magisterial documents, documents of various Christian denominations and research of theologians in this field.